Dawson waterfront showing docks, steamboats and canoes on shore, Dawson, approximately 1898 - Hegg, Eric A., 1867-1948 (1898)
Caption on image: Steamboat landing. Dawson City N.W.T. E.A. Hegg. Dawson City PH Coll 557.17